Stimulating Motivational Engagement in Vocabulary Learning: Evidence From the Word Tail Game in an EFL Classroom - Harsinda; Wahyu; Siti Nurul Ilmi Hl.; Siti Uswatun Khasanah (Media Publikasi Cendekia Indonesia, 2025)
Vocabulary learning is an essential component of English language development, yet many students continue to face difficulties in achieving progress and maintaining motivation. This study aimed to examine the effect of the Word Tail Game on students’ vocabulary achievement and learning motivation. A mixed method approach with a convergent parallel design was employed. Quantitative data were used to measure students’ achievement, and qualitative interview data were used to explore their motivation. The participants consisted of 20 second-grade junior high school students. The findings show a significant increase in post-test scores, indicating an improvement in vocabulary achievement. Qualitative results also reveal that indicators of motivated learning behavior appeared consistently during the game, supported by students’ positive responses. These findings suggest that the Word Tail Game can enhance engagement and support vocabulary learning. The study contributes empirical evidence to the growing body of research on game-based learning in EFL contexts.